Research on the influence of green finance policy on enterprise green innovation - Zhou, Xun (Transactions on Economics, Business and Management Research, 2024)
At present, China's economy has entered a new normal, and policies with economic growth as the core can no longer meet the needs of social development. In recent years, China has vigorously promoted the green transformation of economic development, and the construction of a green innovation system has become the only way to improve the ecological environment and promote green development. Green finance, as a financial tool providing services for green industries such as energy conservation, emission reduction and pollution prevention and control, plays an important role in the process of economic green transformation. Green Finance Reform and Innovation Pilot Zone is the latest practice of green finance policy system construction. Under this background, this paper takes the establishment of our country’s Green Finance Reform Innovation Experimental Zone as a quasi-natural experiment, and adopts the panel data of Shanghai and Shenzhen A-share listed companies from 2011 to 2022, this paper discusses the impact of Green Finance Policy on enterprise green innovation by means of multi-period double difference model. The study found that the policy has an obvious driving effect on enterprise green innovation, and the conclusion passed the parallel trend test and placebo test; in addition, the mechanism test results show that the stronger the financing constraints, the promotion effect of green financial innovation policy may weaken.